Passive gust alleviation of a flying-wing aircraft by analysis and wind-tunnel test of a scaled model in dynamic similarity - He, Shun; Guo, Shijun; Liu, Ying; Luo, Wukui (Elsevier, 2021)
An investigation was conducted to evaluate the effectiveness of a passive gust alleviation device (PGAD) installed in a flying-wing aircraft of 62.3m wing span at large swept back angle. It was performed by numerical analysis and validated by wind-tunnel test of a 1:25 reduced scale physical model of dynamic similarity to the full-scale aircraft. The 1-cosine gust model with a range of gust parameters specified in the airworthiness regulation CS-23 was taken in the gust response analysis that led to 7~9% gust alleviation results by employing the PGAD. The gust response dominated by the first three modes of the aircraft was most critical in the frequency close to the first bending mode of the wing. The wind-tunnel test model was designed and manufactured based on dynamic scaling law, and proved to be of excellent dynamic similarity by the deviation of less than 5.5% between the first three modes of the physical model measured by vibration test and the full-scale aircraft model. The wind tunnel test results show that the gust response of the model in the specified range was reduced by 8.3~14.3% according to the measured wing tip deflection associated with the PGAD oscillation amplitude at 4.0°~15.5°. The present study shows that the numerical analysis of gust response and alleviation of a full-scale aircraft installed with PGAD can be validated by wind tunnel test of a scaled physical model with dynamic similarity.
Keywords: Wind-tunnel test; Dynamic similarity; Passive gust alleviation; Flying-wing aircraft